The multi-dimensional characterization of Al-doped CuO thin films by laser-induced breakdown spectroscopy (LIBS) with nanosecond and picosecond lasers. (January 2023) - Wu, Jiasen; Xia, Xiangyu; Gao, Qing; Xin, Yangmei; Li, Zhao; Xiu, Junshan; Liu, Huiqiang
Abstract: Glasses coated with various optical thin film materials are widely used in people's life and scientific research. In this study, a series of aluminum-doped (Al-doped) copper oxide (CuO) thin films with different sputtering pressures and powers were deposited on soda-lime glass substrates by RF-magnetron sputtering to explore the effect of doping element on the optical properties of the thin films. However, laser-induced breakdown spectroscopy (LIBS) with nanosecond and picosecond lasers was employed to achieve the multi-dimensional analysis of the Al element. With ns-LIBS, the rapid quantitative analysis was performed by drawing the calibration curves of LIBS intensity ratio of Al/Cu versus concentration ratio under different sputtering pressures and powers. Furthermore, the 2D chemical mappings were drawn to provide a more complete and detailed relative spatial distribution of the Al element according to the LIBS intensity ratio of Al/Cu. Meanwhile, the thin film thickness was determined by the picosecond laser pulse number since the depth ablated by a single laser pulse was assessed as nearly 46.75 ± 4.25 nm. Moreover, the variation trends of optical band gaps with sputtering parameters were similar to that of LIBS intensity ratios with sputtering parameters, as suggested by analyzing the transmission spectra of thin films. The results demonstrated that the multi-dimensional characterization (quantitative analysis, 2D chemical mapping, thin-film thickness estimation, and optical properties analysis) of Al-doped CuO thin films prepared by RF-magnetron sputtering can be effectively realized by LIBS. Highlights: The laser induced breakdown spectroscopy (LIBS) system for multi-dimensional characterization of thin films was set up. Rapid analysis of aluminum-doped copper oxide (CuO) thin films was achieved by LIBS. The 2D mappings of LIBS intensity ratio of doped element in thin films were achieved. The depth ablation accuracy of the thin film was nearly 46.75 ± 4.25 nm. The LIBS characterization be employed to assess the optical properties of thin films.